An achievement test in Pilipino for grade four pupils of different linguistic backgrounds - Arellano, Lourdes Agoncillo 1930- (s.n.], 1970)
The objective of the study is to design an achievement test in Pilipino for Grade IV pupils of different linguistic backgrounds, particularly those in the Divison of Quezon City and other school divisions where pupils learn Pilipino as a second a language. This is done to find out whether or not the predicted language difficulties in Pilipino have been overcome. Statistical findings show that the constructed achievement test is valid and reliable and can be used in school divisions where the population is made up of pupils of different linguistic backgrounds.